(3QSGdI GdJbOjS OYGA GdSGObjf (B( (3OYGA GdfLGI GdehMOjf GdYGQajf (B)s - (3MeRI Hf Ydj Hf CMeO GdaGQSqj GdMGcej GdOQRj , J (B433 (3g`s
(3ChdgG (B:s
(3JhcdJ Ydi ehdGfG GdMGce GdeYHhO hMOg GdefLR dYHOg GdEeGe GdgGOi hYOg JhcdJ Ydi ehdGfG MGce GdYbd s
(3BNQgG (B:s
(3hCegdfG dEfLGR hYOc dChdjGFc GdeNdUjf Efc Ydi Pdc bOjQ hHELGHI gPG GdbSe hHEMdGd CdhgjJc cajd LOjQ Je GdJbOjS hGdMeO dehdGfG hMOg hgh MSHi hfYe GdeYjf GdfUjQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B32s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis